Analisis Pengaruh Kompensasi dengan Konsep 3P terhadap Kepuasan Kerja Karyawan (Studi Kasus Hotel Pariwisata Selabintana, Sukabumi) - Maulani, Novi; Trisyulianti, Erlin (Jurnal Manajemen dan Organisasi, 2011)
Each company that was ready to compete must have an effective management. Employee's satisfaction depend on their expectation about what will they get from their compensation. The employees is one of the factors that influence the company’s progress in the Tourism hotel of Selabintana. One of the main employees’s work dissatisfaction factors is compensation that was not in accordance with employee’s expectation. The aim of this research is to analyze the influence of compensation with the concept 3P towards the employee's job satisfaction, to identify the level of the employee's job satisfaction, and to analyze gender relations, the age, the level of education, the length of service, and the number of securities of the family towards the employee's job satisfaction of the Tourism hotel of Selabintana Sukabumi. The data collection used the primary data and the secondary data. The testing of the questionnaire was carried out with the validity test used Pearson product moment and the test reliability used the Alpha Cronbach technique, as well as data processing used the analysis method of the factor, cross tabulation and chi square with SPSS version 15.0 for Windows. The analysis factor’s result that the most influence factor is Pay for Performance factor. The most influence attribute from the factor of Pay for Position is the salary. The most influence attribute from the factor of Pay for Performance is the rotation of the employee. The most influence attribute from the factor of Pay for Competence was the experience. Based on the calculation, the employees generally is in the satisfied category with the value 63.33%.